Journal preface - Team, Editorial (Southern Journal for Contemporary History, 2019)
This is the first issue of the Southern Journal for Contemporary History (SJCH) under the new mandate, the new board and the new editorial team. But just as we set off on a new intellectual and historiographic adventure, it would both be remiss and churlish to do so without a few words of acknowledgement to the previous editors, who kept the Journal for Contemporary History going for more than four decades and the authors who published, leaving a tableau of an evolving historiography and a rich archive for historians of history.